Measuring the thermal resistance of a “metal-thermolectric material” contact structure using a comprehensive absolute method for determining parameters of thermoelectric materials - Lysko, V.V.; Strusovskyi, K.I. (Journal of Thermoelectricity, 2024)
The paper discusses the possibility of measuring the thermal resistance of a” metal-thermoelectric material” contact structure using a comprehensive absolute method for determining the thermoelectric properties of materials. It describes the measurement technique and provides the results of studies of possible measurement errors obtained by constructing a physical model as close as possible to real conditions and computer simulation. The influence of radiation, heat loss through conductors, and other factors on the accuracy of measurements is determined. The conditions for minimizing measurement errors are established.